Context-dependent effects of the CB1 receptor antagonist rimonabant on morphine-induced behavioral sensitization in female mice - Marinho, Eduardo A. V.; Oliveira-Lima, Alexandre Justo; Reis, Henrique S.; Santos-Baldaia, Renan; Wuo-Silva, Raphael; Hollais, Andre W.; Yokoyama, Thais S.; Frussa-Filho, Roberto; Berro, Lais F. (Frontiers in Pharmacology, 2023)
The endocannabinoid system has been implicated in the neurobiology of opioid use disorder. While the CB1 receptor antagonist rimonabant has been shown to block some of the behavioral effects of opioids, studies suggest that the treatment environment (i.e. receiving treatment in the drug-associated environment, and/or novelty) can influence its effects. In the present study, we investigated the role of the treatment environment in the effects of rimonabant on the expression of morphine-induced behavioral sensitization. Adult female Swiss mice were submitted to a behavioral sensitization protocol, during which they received morphine (20 mg/kg, i.p.) in the open-field apparatus, and were subsequently treated with vehicle or rimonabant (1 or 10 mg/kg, i.p.) either in the open-field, in the home-cage or in an activity box (novel environment). The expression of conditioned locomotion (increased locomotor activity in the open-field apparatus in the absence of morphine) and of morphine-induced behavioral sensitization (increased locomotor activity in animals sensitized to morphine) was evaluated during asubsequent saline and morphine challenge, respectively. Animals treated with morphine expressed behavioral sensitization, showing a significant increase in locomotor activity over time. Animals sensitized to morphine and treated with vehicle in the home-cage expressed conditioned locomotion, an effect that was blocked by home-cage treatment with rimonabant. During a saline challenge, only animals sensitized to morphine and treated with saline in the home-cage expressed morphine-induced conditioned locomotion. All morphine-treated animals that received saline during the treatment phase (control groups) expressed behavioral sensitization during the morphine challenge. Treatment with rimonabant in the open-field and in the activity box, but not in the home-cage, blocked the expression of morphine-induced behavioral sensitization. Our findings suggest that CB1 receptor antagonism can modulate conditioned responses to morphine even when administered in the home-cage. However, exposure to the drug-associated environment or to a novel environment is necessary for the expression of rimonabant’s effects on morphine-induced behavioral sensitization during a morphine challenge.